Perangkat Lunak Bantu Pendaftaran Peserta Ujian (DPU) Pada Sekolah Dasar (SD) di Dinas Pendidikan dan Kebudayaan Kota Pagar Alam Berbasis Web - Bhebeind Aryanto Phubenast; Risnaini Masdalipa (Jurnal Nasional Ilmu Komputer, 2021)
Management of Primary School (SD) Exam Participant Registration (DPU) at the Pagar Alam City Education and Culture Office is currently still done manually, namely by recording it in a ledger then the operator manages the data using Microsoft word and Microsoft Excel so it takes a long time to get good results. With the new system that can later create data processing effectively and efficiently, for this success a better system of data processing software is needed as a tool to reduce the error rate in the data search process for Primary School Exam Participant Registration (DPU). (SD). The method used in this research is the waterfall method which has the following sequence of communication, planning, modeling, construction and distribution. Based on the summary above, the authors are interested in raising the Software for Assisting Exam Participant Registration (DPU) in Elementary Schools (SD). At the Department of Education and Culture of the City of Pagar Alam.